Juridical Implications and Welfaee In Fixed-Time Work Agreements - Erlina, Yoshi; Yuhelson, Yuhelson; Akkapin , Suppaphorn (Journal Evidence Of Law, 2025)
This study examines the juridical implications of the Fixed-Time Work Agreement (PKWT) on the welfare of workers in Indonesia. The regulations regulated in Law Number 13 of 2003 concerning Manpower show that there is an imbalance in legal protection between PKWT workers and workers with Indefinite Time Work Agreements (PKWTT). In many cases, PKWT causes job uncertainty, low sense of security, and lack of access to basic workers' rights. This study uses a normative approach with a qualitative analysis of regulations and their implementation. The main findings show that the implementation of PKWT has not fully met the principles of justice and welfare, so it is necessary to revise regulations and policies to protect workers